Synthesis, crystal structures, dielectric and magnetic properties of manganese sulfonyldibenzoates - Balendra; Singh, Bharti; Banday, Azeem; Tewari, Shailabh; Kumar, Vineet; Murugavel, Sevi; Joy, P. A.; Ramanan, Arunachalam (Crystengcomm, 2021)
{A systematic investigation of the system manganese(II) salt-H(2)SBA-auxiliary ligand-solvent successfully led to the isolation of six new multidimensional coordination polymers: [Mn-5(2-pic)(2)(DMA)(4)(SBA)(4)]center dot 4DMA (1), [Mn-3(pyzc)(2)(DMF)(H2O)(SBA)(2)]center dot DMF center dot H2O (2), [Mn-5(pyzc)(2)(DMA)(4)(SBA)(4)]center dot 4DMA (3), [Mn-5(mpyzc)(2)(DMA)(4)(SBA)(4)]center dot 4DMA (4), [Mn-2(phen)(2)(H2O)(SBA)(2)]center dot 2DMA (5) and [Mn-3(phen)(2)(SBA)(3)]center dot 5DMF (6), where SBA = 4,4'-sulfonyldibenzoate 2-pic = 2-picolinate